Development of Leaf Color Level Sensors for Measuring the Nutritional Need of Chrysanthemum based on Raspberry pi - Arifin, Syamsul; Christa; Firgiyanto, Refa; Putra, Dhanang Eka (Food and Agricultural Sciences : Polije Proceedings Series, 2020)
Chrysanthemum (Chrysantium Morifolium) is one of the most popular ornamental flower plants in Indonesia. The advantages of chrysanthemum include adjustable flowering properties so that they can be produced all year round with varied flowers and easier handling. Apart from being used as cut flowers, chrysanthemum plants can be used as traditional medicine and also as insect poison medicine. The quality of chrysanthemums is largely determined by external appearances such as stalks, leaves, and flower crowns. So that it takes an intensive maintenance effort from seeding to harvesting in order to obtain good flower quality. One of the factors that greatly influence the maintenance of chrysanthemum is the provision of nutrients or nutrients. Lack of nutrients in the chrysanthemum will inhibit growth so that it can reduce the quality of the flowers produced. In this paper, a camera-based sensor is developed to measure the color level of chrysanthemum leaves. Leaf color levels were measured through histogram processing on the raspberry pi device. Image processing results are compared with the standard Leaf Color Chart (LCC) to obtain accurate readings.